Numerical Investigation of the Pulsatile Flow of Viscous Fluid in Constricted Wall Channel with Thermal Radiation (Advances in Applied Mathematics and Mechanics, 2023)
The main theme of the current article is to investigate the heat transfer inthe pulsatile flow of an electrically conducting viscous fluid in a constricted channelunder the effect of the magnetic field and thermal radiation. The unsteady governing equations simplified for low conducting fluids are solved numerically by finitedifference method using stream-vorticity function formulation. The influence of theflow parameters such as the Hartmann number (magnetic parameter), Strouhal number (flow pulsation parameter), Prandtl number, and radiation parameter is studied onthe relevant flow profiles. The influence of different emerging parameters on the skinfriction coefficient and Nusselt number are examined, as well. In general, the profilesare observed to exhibit a relatively more regular pattern upstream of the constructionthan that downstream of the constriction.